Pengaruh Profesionalisme Terhadap Intensitas Kerja Karyawan Pada Koperasi Perusahaan Air Minum Tirta Mahakam Kabupaten Kutai Kartanegara - Ilham, Ilham (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2017)
The purpose of this research was to know how much the influenced of the Professionalism affect on Employee Work Itensity on Tirta Mahakam Mineral Water Company in Kutai Kartanegara Regency. The study was conducted in September 2016,with the population data in September 2016 was 10 employees and the number of samples used in this study were 10 employees. The analytical tool used is simple regression analysis and hypothesis testing using t test with SPSS Program. The conclusion in this study that there is a significant influence between Professionalism with Work Itensity Employees at Regional Water Company Cooperative Tirta Mahakam. Thus the hypothesis proposed by researchers in this study are: